ONLINE PRESENTATION AND PROMOTION OF CULTURAL CONTENT IN THE TIME OF THE CORONAVIRUS PANDEMIC ON THE EXAMPLE OF TWO NATIONAL INSTITUTIONS OF THE REPUBLIC OF MACEDONIA (Heritage, 2022)
The subject of research interest is the presentation and promotion of cultural content in the period of the coronavirus pandemic via the social network Facebook by the NI Archaeological Museum and the NI Drama Theater from the Republic of Macedonia (RM).The main research question is: “How did the selected national cultural institutions from RM present and promote cultural content during the first months of the coronavirus pandemic via the social network Facebook?” The aim of the research is to identify: ways of using the social network Facebook by selected national cultural institutions during the first months of the coronavirus pandemic to present and promote cultural content and, thus, to communicate with its audience; presented and promoted cultural content; and changes in the way of presenting and promoting cultural content, that is usually followed live, within the virtual space.As a methodological technique, we used qualitative content analysis.
Keywords: Archaeological Museum, Drama Theater, social networks, Facebook, cultural content, cultural institutions, coronavirus pandemic, Republic of Macedonia